Sintesis Dan Karakterisasi Hidroksiapatit (HAp) Dari Kulit Kerang Darah (Anadara Granosa) Dengan Proses Hidrotermal - Khoirudin, Mukhlis; Yelmida, Yelmida; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Hydroxyapatite Ca10(PO4)6(OH)2 is a material that recently used as a filler and coating for bone and teeth implant. It is used as an implant because it has a good bioactive and biocompatible characteristics. HAp synthesis can be made by using material which is rich of CaCO3 like blood cockle shell (Anadara granosa) (98,7 %). In this research, blood cockle shell whichhas calcium source was synthesized to HAp by hydrothermal process. The size of blood cockle was varied (60, 100, 200 mesh) and reaction duration (16, 20, 24 hours). The outcome of synthesis was characterized by using with FTIR, XRD, SEM-EDX. From FTIR, it showed that hydroxyapatite was formed with the presence of the peak from ion PO43- dan OH. The highest peak was obtained from 200 meshes of particle size for 24 hours. XRD results showed the peaks of hydroxyapatite diffraction pattern with HAp standard at angle 2θ is 10.8322°, 21.7774°, 25.9091°, 28.1308°, 34.1252° with JCPDS hydroxyapatite standard. The form of crystal was hexagonal. SEM-EDX showed the morphology size which was 10µm - 100µm range and 1,99in Ca/p ratio.  Keywords: Blood Cockle Shell,Synthesis,Hydroxyapatite, Hydrothermal Method.